2017
DOI: 10.1016/j.mcna.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndromes

Abstract: Synopsis Myelodysplastic syndrome (MDS) is a heterogeneous, clonal stem cell disorder of the blood and marrow typically diagnosed based on the presence of persistent cytopenia(s), dysplastic cells, and genetic markers. Common issues that arise in the clinical management include difficulty confirming MDS diagnosis, lack of a standard approach with novel agents in MDS, and few prospective long-term, randomized-controlled MDS clinical studies to guide allogeneic blood and marrow transplant. With the recent geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
0
9
1
1
Order By: Relevance
“…In this cohort, the disease was more frequent in females, with a ratio of 1:2.5 and the mean age at diagnosis was 53.8 years. These findings were not in agreement with those of Bănescu et al (2011) and Dao (2017) who found that male are affected more than females with a male/female ratio of 1.44 to 1 and 1.26 to 1, respectively. Despite data from population-based registries on the incidence and prevalence of MDS, other reports also show a predominance of the disease in males (Gologan, 2010;Neukirchen et al, 2011;Lubeck et al, 2016).…”
Section: Discussioncontrasting
confidence: 90%
“…In this cohort, the disease was more frequent in females, with a ratio of 1:2.5 and the mean age at diagnosis was 53.8 years. These findings were not in agreement with those of Bănescu et al (2011) and Dao (2017) who found that male are affected more than females with a male/female ratio of 1.44 to 1 and 1.26 to 1, respectively. Despite data from population-based registries on the incidence and prevalence of MDS, other reports also show a predominance of the disease in males (Gologan, 2010;Neukirchen et al, 2011;Lubeck et al, 2016).…”
Section: Discussioncontrasting
confidence: 90%
“…Myelodysplastic syndrome (MDS) comprises a heterogeneous group of clonal myeloid disorders characterized by debilitating peripheral blood cytopenias, abnormal blood cell development, and clonal genetic markers1. MDS is typically considered as a neoplasm because of frequent genetic aberrations, limited patient survival, and progression to acute myeloid leukemia (AML) 2.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in massively parallel sequencing technology have enabled the genetic characterization of MDS over the last five years, to the point where the focus has now shifted to translating these findings to improve patient outcomes. Further, in the last 10 years, the Food and Drug Administration has approved the use of three MDS therapeutics, in addition to several groups genetically characterizing MDS to a greater extent than before [ 8 ]. The genetic data will assist in diagnosing MDS with equivocal pathologic data and will eventually improve the use of novel and existing drugs, whether they be monotherapies or combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic data will assist in diagnosing MDS with equivocal pathologic data and will eventually improve the use of novel and existing drugs, whether they be monotherapies or combination therapies. Moreover, these data will enhance the treatment of MDS patients post-allogeneic bone marrow transplant (BMT) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%